2000
DOI: 10.1002/(sici)1096-8644(2000)112:2<191::aid-ajpa6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in cortical modeling in the femoral mid-shaft: Sex and age differences

Abstract: Modern lifestyle changes may result in site-specific alterations in the skeleton. Our aim was to determine sex and age differences in regional geometry at the mid-femur. Complete cross sections from 113 individuals aged 20-97 years from a modern Australian population were obtained. A further subsample of 24, in whom the precise orientation of specimens was known, was subsequently collected. Microradiographs were made of 100-microm sections and the bone was analyzed using image processing software (Optimas, Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 46 publications
2
34
2
Order By: Relevance
“…The statistically significant thinner cortex in older compared to the younger subjects in the anterior region, with similar trend medially and laterally, is in agreement with previous microradiographic findings on femoral midshaft sections from female donors of age similar to this study [29]. Moreover, in both the age groups, the Ct.Th tended to be thinnest anteriorly compared to medially and laterally, in agreement with earlier reports [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The statistically significant thinner cortex in older compared to the younger subjects in the anterior region, with similar trend medially and laterally, is in agreement with previous microradiographic findings on femoral midshaft sections from female donors of age similar to this study [29]. Moreover, in both the age groups, the Ct.Th tended to be thinnest anteriorly compared to medially and laterally, in agreement with earlier reports [29].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in both the age groups, the Ct.Th tended to be thinnest anteriorly compared to medially and laterally, in agreement with earlier reports [29].…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that these differences stem from the fact that femoral cortical bone morphology undergoes more complex changes throughout life in response to weight bearing compared to the non-weight bearing metacarpal cortical bone. A number of studies have documented the changes in femoral cortical bone geometry with increased age between the sexes [11,17,18]. In a study on modern autopsy femoral samples Feik et al [18] found that whilst elderly men and women resemble each other in the circularity of their femoral shafts, significant differences were apparent in bone dimensions between middle and older aged females and younger and middle aged males.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have documented the changes in femoral cortical bone geometry with increased age between the sexes [11,17,18]. In a study on modern autopsy femoral samples Feik et al [18] found that whilst elderly men and women resemble each other in the circularity of their femoral shafts, significant differences were apparent in bone dimensions between middle and older aged females and younger and middle aged males. Most notably, Feik et al [18] identified a greater antero-posterior distribution of bone in the young adult males, compared with more circular shafts in the females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation